Norbit - Davis, John, 1954-; Murphy, Eddie, 1961-; Murphy, Charlie, 1959-2017; Scherick, Jay; Ronn, David; Robbins, Brian, 1963-; Newton, Thandiwe, 1972-; Griffin, Eddie, 1968-; Crews, Terry, 1968-; Gooding, Cuba, Jr., 1968-; Newman, David, 1954-; Baker, Rick, 1950-; et al. (Universal City, California DreamWorks Home Entertainment, 2007)
Mild-mannered Norbit has a second chance at love with his childhood sweetheart, but the one major obstacle standing in his way is jealous Rasputia, his larger-than-life fiancee.
Originally produced as a motion picutre in 2007.
Widescreen.
Special features: 14 deleted scenes; The making of Norbit; Man of a thousand faces; Power tap (Marlon Wayans mock infomercial); The stunts of Norbit; photo gallery; theatrical trailer.
Music by David Newman ; special make-up effects by Rick Baker ; costume designer, Molly Maginnis ; film editor, Ned Bastille ; production designer, Clay A. Griffith ; director of photography, Clark Mathis.
Eddie Murphy, Thandie Newton, Eddie Griffin, Terry Crews, Cuba Gooding, Jr.
MPAA rating: PG-13; for crude and sexual humor, some nudity and language.
Keywords: Overweight women -- United States -- Drama; Triangles (Interpersonal relations) -- United States -- Drama; Betrothal -- United States -- Drama; Jealousy -- Drama; United States; Videodiscs; DVD-Video discs; Feature films; Comedy films; Video recordings for the hearing impaired; Drama